Pemahaman Mahasiswa Dalam Berinvestasi Saham Di Pasar Modal Syariah Menurut Maqasyid Al Syariah (Studi Kasus STAI JM Langkat) - Syafitri Ayu Gustika (Peduli Riset dan Pengabdian Masyarakat, 2024)
This research focuses on discussing STAI JM Langkat students' understanding of sharia stock investment in the sharia capital market and discussing sharia stock investment in the sharia capital market according to maqasyid al sharia. The research method used in this research is a descriptive qualitative research method with an empirical approach. In this research, researchers used data collection techniques by means of interviews, literature study and documentation. With respondents of 100 students. 25 students each semester I, III, V and VII. The research has different results from each semester level which can be categorized as follows: first semester students do not understand sharia stock investment, third semester students' understanding of sharia stock investment is still very low, fifth semester students understand enough about sharia stock investment and VII semester students really understand about sharia stock investment. STAI JM Langkat students' understanding of sharia stock investment in the sharia capital market varies from each semester level which can be categorized as follows: first and third semester students do not understand sharia stock investment in the sharia capital market, fifth semester students understand enough about stock investment sharia in the sharia capital market and seventh semester students really understand about sharia stock investment in the sharia capital market. According to Maqasyid al Syariah.